Crime at places and spatial concentrations: exploring the spatial stability of property crime in Vancouver BC, 2003–2013 - Andresen, Martin A. (Journal of quantitative criminology, 2017)
Objectives Investigate the spatial concentrations and spatial stability of criminal event data at the micro-spatial unit of analysis in Vancouver, British Columbia. Methods Geo-referenced crime data, 2003–2013, representing four property crime types (commercial burglary, mischief, theft from vehicle, theft of vehicle) are analyzed considering crime concentrations at the street segment and street intersection level as well as through the use of a nonparametric spatial point pattern test that identifies the stability in spatial point patterns in pairwise and longitudinal contexts. Results Property crime in Vancouver is highly concentrated in a small percentage of street segments and intersections, as few as 5 % of street segments and intersections in 2013 depending on the crime type. The spatial point pattern test shows that spatial stability is almost always present when considering all street segments and intersections. However, when only considering the street segments and intersections that have crime, spatial stability is only present in recent years for pairwise comparisons and moderately stable in the longitudinal tests. Conclusions Despite the crime drop that has occurred in Vancouver, there is still spatial stability present over time at levels suitable for theoretical development. However, caution must be taken when developing initiatives for situational crime prevention.